2014
DOI: 10.1021/ci500585w
|View full text |Cite
|
Sign up to set email alerts
|

Best of Both Worlds: Combining Pharma Data and State of the Art Modeling Technology To Improve in Silico pKa Prediction

Abstract: In a unique collaboration between a software company and a pharmaceutical company, we were able to develop a new in silico pKa prediction tool with outstanding prediction quality. An existing pKa prediction method from Simulations Plus based on artificial neural network ensembles (ANNE), microstates analysis, and literature data was retrained with a large homogeneous data set of drug-like molecules from Bayer. The new model was thus built with curated sets of ∼14,000 literature pKa values (∼11,000 compounds, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 46 publications
(64 reference statements)
1
107
0
Order By: Relevance
“…They showed that training can reduce the average prediction error for new chemotypes to what is observed for public domain data. A similar study was published by Fraczkiewicz et al 18 for the pKa prediction method from Simulations Plus. The initial model was trained on about 14,000 literature pKa values.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…They showed that training can reduce the average prediction error for new chemotypes to what is observed for public domain data. A similar study was published by Fraczkiewicz et al 18 for the pKa prediction method from Simulations Plus. The initial model was trained on about 14,000 literature pKa values.…”
Section: Introductionmentioning
confidence: 60%
“…18,34 As the MoKa software is not differentiating between macro-and microconstants in the training, we need to consider this problem in our curation effort by not blindly assigning experimental pKa values to ionization sites. Instead we restrict the assignment to cases where we can unambiguously make it and where the macroconstant is a good approximation of the microconstant.…”
Section: Assignment Of Experimental Pk a Values To Ionization Sitesmentioning
confidence: 99%
“…First, protonation states at pH 7.4 for co-crystallized ligand, ChEMBL hits and library compounds were calculated using the pKa module co-developed by Bayer and SimulationPlus [31] and implemented as Pipeline Pilot component "ADMET predictor" [32], while ring conformers, tautomers and stereoisomers were generated using Schrödinger LigPrep utility, release 9.8.…”
Section: Dockingmentioning
confidence: 99%
“…Amino acids with different side chain orientations responsible for change in pocket shape are shown as sticks. SiteMap [31] generated surfaces are shown in blue mesh for 3G1M and magenta mesh for 3O8H; b) Overlay of the crystallized 3G1M ligand (green), the crystallized_3O8H ligand (cyan) and the docking pose of the 3O8H ligand in 3G1M (magenta). for our designed oxadiazole library.…”
Section: A) Ab)mentioning
confidence: 99%
“…Many of the errors described were discovered (and corrected) while curating data sets used in constructing some of the many models distributed as part of ADMET Predictor TM [7]: our pK a model [8]; cytochrome P450 (CYP) site-of-metabolism models for CYPs 1A2, 2A6, 2B6, 2C8, 2C9, 2C19, 2D6, 2E1 and 3A4 and their associated substrate classification models; and kinetic models (inhibition, K m , V max and intrinsic clearance (CL int )) for the five major CYPs-1A2, 2C9, 2C19, 2D6 and 3A4. Others were discovered in the course of selecting a reference subset of the World Drug Index (WDI) [9] to set thresholds of concern (ADMET Risk TM thresholds) for 40 other ADMET models currently included in ADMET Predictor's ADMET Risk TM score.…”
Section: Introductionmentioning
confidence: 99%